Gambaran dukungan keluarga terhadap pengobatan remaja penyandang Thalasemia - Indah Permata Artamia; Windy Rakhmawati; Iwan Shalahuddin (Holistik Jurnal Kesehatan, 2019)
Family support in adolescents with thalassemia undergoing treatmentBackground: Thalassemia is a chronic disease that affect to body organ caused by the disease itself and medication given in a long term. Compliance of taking medication becomes determing factor of treatment success. Family support is influential factor of therapy success. It includes instrumental support, informational support, assessment support, and emotional support.Purpose: The objective of this research is to know the description of family support therapy of adolescent with thalassemia in Garut.Methods: The method of this research is quantitative descriptive with total sampling technique (N=54) of adolescent with thalassemia population in Garut.Results: The result of this research is most of responden earn high support with maximum value of 70.4%, and medium support with value 29.6%, and there is no respondent with low support. From sub variable result as a whole, they obtained high support which was an instrumental support 70.4%, informational support 64.8%, assessment support 70.4%, and emotional support 53.7%.Conclusion: The result of this research is that most adolescent with Thalassemia obtained high support as many as 70.4%, therefore it can be factor determing therapy receivedKeywords: Family support; Adolescents; Thalassemia; Undergoing treatmentPendahuluan: Thalasemia merupakan penyakit kronis yang berdampak pada organ tubuh disebakan oleh penyakit itu sendiri dan pengobatan yang diberikan dalam jangka panjang. Kepatuhan menjadi faktor yang menentukan keberhasilan pengobatan. Dukungan keluarga merupakan faktor yang mempengaruhi kepatuhan pengobatan, yang meliputi dukungan instrumental, informasional, penilaian, dan emosional.Tujuan: Diketahuinya gambaran dukungan keluarga terhadap pengobatan remaja penyandang Thalasemia di kabupaten Garut.Metode: Metode penelitian ini menggunakan deskriptif kuantitatif dengan teknik pengambilan sampel total sampling (N=54) dengan populasi yaitu penyandang Thalasemia usia remaja di kabupaten Garut.Hasil: Hasil penelitian dukungan keluarga sebagian besar responden mendapatkan dukungan tinggi dengan nilai maksimum yaitu 70.4% dan dukungan sedang dengan nilai minimum yaitu 29.6%, dan tidak terdapat responden yang mendapatkan dukungan rendah, dan dari hasil per subvariabel secara keseluruhan mendapatkan dukungan tinggi yaitu, dukungan instrumental sebesar 77.8%, dukungan informasional sebesar 64.8%, dukungan penilaian sebesar 70.4%, dan dukungan emosional sebesar 53.7%.Simpulan:  dari penelitian ini bahwa remaja penyandang Thalasemia sebagian besar mendapatkan dukungan tinggi sebanyak 70.4%, sehingga dapat menjadi faktor dalam menentukan pengobatan yang diterima